Al-munawar via MOOC : a platform for learning arabic language communication (level 1- beginner) - Wan Ab. Aziz Wan Daud; Ahmad Abdul Rahman; Ahmad Zaki Amiruddin; Ahmed Thalal Hassan; Nor Abdul Rahman; Amanee Abdul Hai (2018)
This project presents an online course known as MOOC Al – Munawwar through the platform openlearning.com based on the ADDIE instructional design model. The online course was designed based on students’ needs, opinions, and suggestions, which will be evaluated by the participants involved in this study, selected among students who are studying the Arabic language Communication level 1. Arabic online Course (Level 1) contains six (6) main chapters divided into 14 lessons for this MOOC offer. Each lesson focuses on the application of four language skills ie; written skills, listening skills, reading skills and basic speaking skills for beginners.